2020
DOI: 10.4269/ajtmh.19-0625
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Detection among Hospitalized Patients, Sarawak

Abstract: Burkholderia pseudomallei infections are prevalent in Southeast Asia and northern Australia and often misdiagnosed. Diagnostics are often neither sensitive nor rapid, contributing up to 50% mortality rate. In this 2018 pilot study, we enrolled 100 patients aged 6 months-79 years from Kapit Hospital in Sarawak, Malaysia, with symptoms of B. pseudomallei infection. We used three different methods for the detection of B. pseudomallei: a real-time polymerase chain reaction (PCR) assay, a rapid lateral flow immunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recent studies reported that several nosocomial infections caused by BCC in countries like Canada, Australia, Thailand, Switzerland, and Saudi Arabia with a few cases leading to the death of the patients 4–7 . Previous reports have substantiated that in the USA and Canada, BCC infections among CF patients were prevalent with an average of 67%, and similar cases have been reported in New Zealand, Australia, and several European countries 3,8 .…”
Section: Introductionmentioning
confidence: 78%
“…Recent studies reported that several nosocomial infections caused by BCC in countries like Canada, Australia, Thailand, Switzerland, and Saudi Arabia with a few cases leading to the death of the patients 4–7 . Previous reports have substantiated that in the USA and Canada, BCC infections among CF patients were prevalent with an average of 67%, and similar cases have been reported in New Zealand, Australia, and several European countries 3,8 .…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, identifying B. pseudomallei and other closely related Burkholderiaceae isolates is a considerable challenge for clinical microbiology laboratories ( Thibault et al., 2004 ). The culture-based method is the gold standard for identifying B. pseudomallei , but it usually takes 3-5 days; therefore, it is easy to miss the optimal time for treatment ( Lee et al., 2005 ; Choi et al., 2020 ). The ELISA method can be used to detect the specific antibodies to B. pseudomallei ( Kohler et al., 2016 ; Suttisunhakul et al., 2016 ; Yatsomboon et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial culture, although specific, may lack sensitivity due to both inadequate sampling and low bacterial loads in clinical samples (Hoffmaster et al, 2015). Other methods of laboratory diagnosis, including direct real-time polymerase chain reaction assays and rapid antigen detection, have not been shown to be more sensitive than bacterial culture (Choi et al, 2020;Currie, 2015). Serological diagnosis, meanwhile, is complicated by the high background sero-positivity among individuals living in endemic areas (Norazah et al, 1996).…”
Section: Introductionmentioning
confidence: 99%